2002
DOI: 10.1128/jvi.76.16.8446-8454.2002
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Aspects of Recombinant Adeno-Associated Virus Delivery to the Mammalian Brain

Abstract: Recombinant adeno-associated viruses (rAAV) are highly efficient vectors for gene delivery into the central nervous system (CNS). However, host inflammatory and immune responses may play a critical role in limiting the use of rAAV vectors for gene therapy and functional genomic studies in vivo. Here, we evaluated the effect of repeated injections of five rAAV vectors expressing different genetic sequences (coding or noncoding) in a range of combinations into the rat brain. Specifically, we wished to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 55 publications
4
75
1
Order By: Relevance
“…Re-expression could be activated as long as 15 months after initial injection and expression, indicating that the transgene is retained within the brain. The study of Mastakov et al 19 demonstrated that repeated administration of rAAV was efficient, induced no host immune response, and resulted in no decrease in transgene expression when the interval between injections was 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Re-expression could be activated as long as 15 months after initial injection and expression, indicating that the transgene is retained within the brain. The study of Mastakov et al 19 demonstrated that repeated administration of rAAV was efficient, induced no host immune response, and resulted in no decrease in transgene expression when the interval between injections was 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the expanded tropism, rAAV5 mediated a more widely dispersed pattern of transduction. Mastakov et al, 15 also reported that rAAV5, as compared to rAAV2, mediated more widespread transgene gene expression within the CNS following direct intracerebral injection. The results of these studies suggest that intraparenchymal diffusion and the ability to transduce non-neuronal cells are a function of the different binding specificities of each vector.…”
Section: Introductionmentioning
confidence: 98%
“…However, as a therapeutic agent in many neurologic disorders, this vector is limited by a small region of transduction following intracerebral administration 9,10 and inefficient transduction of glial and ependymal cells. 1,2,11,12 Coadministration of this vector with heparin [13][14][15] or mannitol 10 alone or in combination with convection-enhanced delivery techniques 13,14 has been shown to increase the region of transduction. Also, it might be possible to redirect rAAV2 tropism to non-neuronal cells through genetic modification of the capsid [16][17][18] and the use of bispecific antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, in contrast, have established that this humoral response has no influence on the efficiency of infection with the vector administered within the muscle 33 or lungs. 34 Similarly, the development of anti-AAV antibodies is minimal or nonexistent after administration of AAV into the brain 35,36 or retina. 37 However, these studies were conducted in animals, which do not have pre-existing anti-AAV immunity, in contrast to humans.…”
Section: Introductionmentioning
confidence: 99%